2019
DOI: 10.5194/acp-19-14571-2019
|View full text |Cite
|
Sign up to set email alerts
|

Sun photometer retrievals of Saharan dust properties over Barbados during SALTRACE

Abstract: The Saharan Aerosol Long-Range Transport and Aerosol-Cloud-Interaction Experiment (SALTRACE) was devoted to the investigation of Saharan dust properties over the Caribbean. The campaign took place in June-July 2013. A wide set of ground-based and airborne aerosol instrumentation was deployed at the island of Barbados for a comprehensive experiment. Several sun photometers performed measurements during this campaign: two AERONET (Aerosol Robotic Network) Cimel sun photometers and the Sun and Sky Automatic Radio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 54 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…For this reason mineral dust particle mi-crophysical properties were updated in the latest OPAC version (v4.0; Gasteiger et al, 2011;Koepke et al, 2015). They are now calculated by means of the T-matrix method (Waterman, 1971) under assumptions of an aspect ratio distribution for prolate spheroids observed during the Saharan mineral dust experiments SAMUM-I and SAMUM-II (Kandler et al, 2009(Kandler et al, , 2011. Several studies have shown that T-matrix theory substantially improves the agreement between measured and modeled aerosol optical properties of aspherical mineral dust particles (Mishchenko et al, 1997;Kahnert et al, 2005;Gasteiger et al, 2011) and are thus motivating its use in this study.…”
Section: Opac Aerosol Microphysical Propertiesmentioning
confidence: 99%
“…For this reason mineral dust particle mi-crophysical properties were updated in the latest OPAC version (v4.0; Gasteiger et al, 2011;Koepke et al, 2015). They are now calculated by means of the T-matrix method (Waterman, 1971) under assumptions of an aspect ratio distribution for prolate spheroids observed during the Saharan mineral dust experiments SAMUM-I and SAMUM-II (Kandler et al, 2009(Kandler et al, , 2011. Several studies have shown that T-matrix theory substantially improves the agreement between measured and modeled aerosol optical properties of aspherical mineral dust particles (Mishchenko et al, 1997;Kahnert et al, 2005;Gasteiger et al, 2011) and are thus motivating its use in this study.…”
Section: Opac Aerosol Microphysical Propertiesmentioning
confidence: 99%
“…Over the last few years these lidars have become widely used in wind and turbulence studies (e.g. Päschke et Vakkari et al, 2015;Tuononen et al, 2017;Manninen et al, 2018). Additionally, depolarization ratio measurements by Halo lidars have been used to study cloud and precipitation phase (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As the fine-mode PSD has a negligible impact on dust optical properties 495 in TIR, the result suggests that the AERONET coarse-mode PSD is highly likely to be underestimated in terms of size, which has been pointed out in several studies comparing AERONET PSD with other in-situ measurements (Müller et al, 2010;Müller et al, 2012;Mcconnell et al, 2008;Adebiyi et al, 2023). Due to the difficulties of comparing the PSD from the column-integrated retrieval to that from the lofted-layer measurement (Toledano et al, 2019), the possible reasons are as-of-yet not well-explained, which require detail investigations in the future. 500…”
mentioning
confidence: 86%